2003
DOI: 10.1055/s-0037-1613435
|View full text |Cite
|
Sign up to set email alerts
|

A single complete ultrasound investigation of the venous network for the diagnostic management of patients with a clinically suspected first episode of deep venous thrombosis of the lower limbs

Abstract: SummaryIn patients clinically suspected of deep-vein thrombosis (DVT) of the lower limbs, it is safe to withhold anticoagulant therapy after a negative ultrasound (US) limited to the popliteal and the femoral veins, provided that this can either be repeated or combined with other diagnostic procedures. To assess the safety of withholding anticoagulants after a single negative complete US, we performed a multicenter, prospective, cohort study including consecutive ambulatory outpatients from institutional and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…25 Some studies by highly skilled ultrasonographers who used the best ultrasound machines reported much higher accuracy. 26 The improvement in ultrasound technology and increased experience in the field have led to a reliable diagnosis of distal DVT in experienced hands when the most reliable diagnostic criterion is used: the lack of compressibility of a venous segment.…”
Section: Various Lower-limb Venous Ultrasound Strategies For Suspecte...mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Some studies by highly skilled ultrasonographers who used the best ultrasound machines reported much higher accuracy. 26 The improvement in ultrasound technology and increased experience in the field have led to a reliable diagnosis of distal DVT in experienced hands when the most reliable diagnostic criterion is used: the lack of compressibility of a venous segment.…”
Section: Various Lower-limb Venous Ultrasound Strategies For Suspecte...mentioning
confidence: 99%
“…Seven prospective outcome studies that used a single complete (ie, proximal, distal) CUS have been published (Table 2). 11,26,[31][32][33][34][35] Patients were treated if CUS showed a proximal or distal DVT and were left untreated if proximal and distal veins were normal without further testing. These studies confirmed the safety of a single complete CUS, with a pooled estimate of the 3-month thromboembolic risk of 0.6% (95% CI, 0.3%-0.9%).…”
Section: Various Lower-limb Venous Ultrasound Strategies For Suspecte...mentioning
confidence: 99%
“…DVTs are classified based on the anatomical site of involved venous segments. A proximal DVT may involve popliteal, femoral, and iliac veins, and the inferior vena cava (IVC) (8), while isolated distal deep vein thrombosis (IDDVT), or calf DVT, that represents around 30-50% of all lower-limb DVTs, does not extend to proximal veins (9)(10)(11). Although there is evidence that IDDVT may spontaneously resolve (12), there are reports of it extending proximally and leading to PE with a combined risk of proximal propagation and PE ranging between 7.8 and 11.4% (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%